The mismeasure of Terry stops: Assessing the psychological and emotional harms of stop and frisk to individuals and communities. (25th March 2019) - Bandes, Susan A.; Pryor, Marie; Kerrison, Erin M.; Goff, Phillip Atiba
Abstract: In Terry v. Ohio, the US Supreme Court relied on a balancing test to uphold the reasonableness of the practice known as "stop and frisk, " balancing the contribution of the practice to effective crime prevention and detection against the nature and quality of the intrusion to individual rights. In recent years, statistics have been powerfully deployed by legal scholars, jurists, and policymakers to challenge the assumption that stop and frisk leads to frequent discovery of contraband or other criminal behavior, and to address stark racial and ethnic disparities in the deployment of stop and frisk. However, the other side of the Terry equation—the nature and quality of the intrusion—has received far less attention from the legal community. With few exceptions, Terry jurisprudence portrays the Terry frisk simply as a brief pat‐down of the outer clothing and treats each Terry stop as an isolated encounter for purposes of measuring the harm involved. Yet there is a robust social science literature on the effects of stop and frisk on individuals, including data on its effects on individuals from marginalized or vulnerable groups, on individuals over time, and on communities as a whole. Moreover, stop and frisk in the current era has evolved from a tool in the arsenal of individual officers to a systematic, widely deployed strategy. This article argues that the failure to grapple with the application of modern knowledge to modern policing practices leads to a mismeasurement on both sides of the Terry equation. Not only does stop and frisk cause a wide range of emotional and psychological harms; these harms may also interfere with the ability of law enforcement to prevent and investigate crime. Even apart from any legal doctrinal implications for stop and frisk jurisprudence, recognizing the flawed assumptions described in this article should encourage all the relevant stakeholders to re‐evaluate the consequences of the Terry regime.